Prevalence and predictors of homophobic behavior among high school students in Switzerland. Issue 2 (3rd April 2018) - Weber, Patrick; Gredig, Daniel
ABSTRACT: This study assessed homophobic verbal behavior among high school students in Switzerland and tested a multifactorial explanatory model. Data were collected by a self-administered questionnaire and analyzed using descriptive statistics and structural equation modeling. Of the 897 students, 85.4% reported having made homophobic statements in the previous 12 months. Behavior was predicted by negative attitudes (β = 0.20), acceptance of traditional gender roles (β = 0.06), religiosity (β = −0.07), contact with gay people (β = 0.10), expectations of parents (β = −0.14) and friends (β = −0.19), gender (β = −0.22), and immigration background (β = 0.09). The social cognitive variables were determined by gender, age, immigration background, school type, and discussion of homosexuality in class (GFI = 0.995, AGFI = 0.979, SRMR = 0.0169, CMIN/ df = 1.199, adj. R 2 = 0.384). Findings provide leverage points for interventions.